The Effect of Teacher’s Competence, Student’s Interests, and Student’s Motivation on Student’s Learning Outcomes - Ramadhany, Tazkia; Arafat, Yasir; Putra, Muhammad Juliansyah (Yayasan Sembilan Pemuda Indonesia, 2024)
The results of the Final School Assessment revealed that pupils in class VII of State Middle Schools in the Sungaiselan District had poor learning outcomes in social studies. According to current understanding, both internal and external influences can have an impact on learning outcomes. The goal of this study is to ascertain the effects of internal and external variables on the learning outcomes of class VII students in social studies courses. Internal variables include learning motivation and interest. The learning results of class VII pupils in the Sungaiselan sub-district in social studies are the focus of this study. The use of questionnaires and documentation studies is the research methodology. The Slovin formula was used to establish the sample size in this study, which included 100 students. Proportional random sampling was utilized as the sampling technique. Multiple regression analysis is the method of data analysis that is employed. According to the study’s findings, (i) teacher competence positively affects class VII students’ learning outcomes in social studies subjects in the Sungaiselan District, and (ii) interest in learning positively affects class VII students’ learning outcomes in the social studies subject in the Sungaiselan District. Additionally, class VII students’ learning results in social studies in the Sungaiselan District are positively impacted by their enthusiasm to learn. Additionally, based on all computations, it was determined that H0 was rejected and Ha was accepted, indicating that the variables Teacher Competence (X1), Learning Interest (X2), and Learning Motivation (X3) had an impact on the Learning Outcome variable (Y) when assessed concurrently or simultaneously.